Synthesis of N-peptide-6-amino-D-luciferin Conjugates - Kovács, Anita K.; Hegyes, Péter; Szebeni, Gábor J.; Nagy, Lajos I.; Puskás, László G.; Tóth, Gábor K. (Frontiers in Chemistry, 2018)
A general strategy for the synthesis of N-peptide-6-amino-D-luciferin conjugates has been developed. The applicability of the strategy was demonstrated with the preparation of a known substrate, N-Z-Asp-Glu-Val-Asp-6-amino-D-luciferin (N-Z-DEVD-aLuc). N-Z-DEVD-aLuc was obtained via a hybrid liquid/solid phase synthesis method, in which the appropriately protected C-terminal amino acid was coupled to 6-amino-2-cyanobenzothiazole and the resulting conjugate was reacted with D-cysteine in order to get the protected amino acid-6-amino-D-luciferin conjugate, which was then attached to resin. The resulting loaded resin was used for the solid-phase synthesis of the desired N-peptide-6-amino-D-luciferin conjugate without difficulties, which was then attested with NMR spectroscopy and LC-MS, and successfully tested in a bioluminescent system.